Enhancing sustainability through organically grown linseed under soybean-linseed cropping system: ENHANCING SUSTAINABILITY THROUGH ORGANIC LINSEED UNDER SOYBEAN-LINSEED SYSTEM - SANJAY K DWIVEDI; RAHUL RAJ; HIMALAY SAHU; PRENA JAISWAL (Journal of Oilseeds Research, 2025)
A field experiment was conducted to study the effect of organic sources of nutrient management practices on growth, yield and nutrient uptake of linseed during winter season of 2021-22, 2022-23 and 2023-24. The experiment was laid out in the Randomized Block Design (RBD) with three replications. The soybean crop was grown as preceding rainy crop under common organic management practices. The result showed that application of FYM to supply 33% of recommended N + Neem cake to supply 33% of recommended N + Foliar spray of cow urine (10%) at branching, flowering and capsule development stage (T9) gave higher linseed seed yield (1590 kg/ha), linseed stover yield (3625 kg/ha), and net monetary returns (55440 `/ha) followed by FYM to supply 33% of recommended N + Neem cake to supply 33% of recommended N + Foliar spray of vermiwash (10%) at branching, flowering and capsule development stage (T6) and FYM to supply 33% of recommended N + Neem cake to supply 33% recommended N (T3). However lower linseed seed yield (970 kg/ha), stover yield (2207 kg/ha), and net monetary returns (30080 `/ha) were recorded with the application of Absolute control (No manure or cake application except the common practices of bio-inoculants, preceding legume crop and plant protection) (T10). The highest nitrogen use efficiency (20.2) was recorded under the application of Neem cake to supply 33% of recommended N + Foliar spray of cow urine (10%) at branching, flowering and capsule development stage (T8). Whereas, the highest phosphorus use efficiency (62.8) and potassium use efficiency (59.0) were recorded under the application of Neem cake to supply 33% of recommended N + Foliar spray of vermiwash (10%) at branching, flowering and capsule development stage (T5). The total nutrient up take by grain and stover (43 kg N/ha), (14 kg P/ha) and (63 kg K/ha) were also found higher with the application of FYM to supply 33% of recommended N + Neem cake to supply 33% of recommended N + Foliar spray of cow urine (10%) at branching, flowering and capsule development stage (T9) which might be due to higher yield observed in this treatment. The buildup of organic carbon also followed almost similar pattern of yield. The soybean-based linseed organic nutrient management system was evaluated and the findings revealed that system productivity (1613 kg/ha LEY), production efficiency (6.86 kg/ha/day) and economic efficiency (624.1 `/ha/day) were highest with the application of FYM to supply 33% of recommended N + Neem cake to supply 33% of recommended N + Foliar spray of cow urine (10%) at branching, flowering and capsule development stage (T9).